A Gentleman with Anemia and Cholestasis. (9th November 2010) - Law, Siu-Tong; Lee, Wai-Ki; Li, Michael Kin-Kong; Lok, Ka-Ho
Abstract : Primary sclerosing cholangitis is a rare cause of cholestasis caused by progressive inflammation and fibrosis of both intrahepatic and extrahepatic bile ducts leading to multifocal ductal strictures. Herein, we report a case of primary sclerosing cholangitis and inflammatory bowel disease. The concomitant diagnosis of these two diseases is not typical. The management includes the treatment of inflammatory bowel disease and potential complications of primary sclerosing cholangitis, including dominant strictures of bile duct, portal hypertension, gallbladder diseases, cholangiocarcinoma, and colonoscopic surveillance.